I Reperti e I Motivi Egizi Ed Egittizzanti a Pompei Indagine Preliminare per una Loro Contestualizzazione. - Bellucci, Nikola D. (Archaeopress Roman Archaeology Ser., 2021)
This volume presents a synthesis of research on Egyptian and Egyptianizing material from Pompeii. Starting from the historical context in which to frame these phenomena and proceeding with a review of terminology, the work provides the first up-to-date corpus of Egyptian and Egyptianizing subjects and finds from the famous archaeological site.